The Buen Vivir: A Policy to Survive the Anthropocene?. Issue 1 (16th December 2014) - Calisto Friant, Martin; Langmore, John
Abstract This article examines the ideology and the politics of buen vivir as the government of Rafael Correa in Ecuador has implemented them from 2007 to 2013. The analysis focuses on the implications of this model, which is based on a traditional Andean world view. The article first explores the main components of buen vivir including its focus on strengthening democratic participation and environmental justice. Second, the implementation of this ideology is analysed through a review of the new constitution and government policies. Third, key outcomes are assessed through various social and economic indicators. Fourth, a critical approach to the government's interpretation of buen vivir is taken and the many contradictions and inconsistencies in its implementation are unfolded. Nevertheless, the policies of buen vivir have the potential to create innovative and inspiring solutions, especially in the face of the environmental and social challenges brought by the anthropocene.